A talk with academician SASA Petar Vlahović on his expert stay in PR China - Vesna Vučinić-Nešković (University of Belgrade, 2016)
Academician Petar Vlahović, a retired professor at the University of Belgrade, Faculty of Philosophy is the first, and up to now, only Serbian ethnologist/anthropologist who underwent professional development in the People’s Republic of China. In the period between November 1955 and December 1856 he stayed at the University of Beijing. This interview is dedicated to his stay in China as well as to the ways in which this experience was meaningful to his further development as a teacher and researcher in ethnology and anthropology at the University of Belgrade. The text is based on three interviews with academician Vlahović conducted in November and December 2012 and March 2014.